2016
DOI: 10.1007/s11239-016-1351-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute and long-term effect of percutaneous coronary intervention on serially-measured oxidative, inflammatory, and coagulation biomarkers in patients with stable angina

Abstract: Objectives To derive insights into the temporal changes in oxidative, inflammatory and coagulation biomarkers in patients with stable angina undergoing percutaneous coronary intervention (PCI). Background PCI is associated with a variety of biochemical and mechanical stresses to the vessel wall. Oxidized phospholipids are present on plasminogen (OxPL-PLG) and potentiate fibrinolysis in vitro. We recently showed that OxPL-PLG increase following acute myocardial infarction, suggesting that they are involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…There is some plausibility to the theory of immune induction following an oxLDL stimulus: using PCI as an example ( 43 ), studies have shown long-lasting immune system induction to rapid oxLDL increases, with raised IgG and IgM anti-oxLDL antibodies present out to 6 months following the index procedure ( 9 , 44 ). Whilst these studies demonstrated immunomodulation following PCI, we did not find such a trend in this study, with unchanged baseline or post-exercise oxidative biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…There is some plausibility to the theory of immune induction following an oxLDL stimulus: using PCI as an example ( 43 ), studies have shown long-lasting immune system induction to rapid oxLDL increases, with raised IgG and IgM anti-oxLDL antibodies present out to 6 months following the index procedure ( 9 , 44 ). Whilst these studies demonstrated immunomodulation following PCI, we did not find such a trend in this study, with unchanged baseline or post-exercise oxidative biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Is circulating oxLDL transported from solid tissue or oxidized in the blood? For example, in patients undergoing PCI, the peak of oxidized phospholipids immediately increases after surgery, and the effect of immunoglobulin (Ig) on oxLDL decreases (Leibundgut, Lee, Strauss, Segev, & Tsimikas, 2016). However, the presence of oxLDLs has been confirmed in atherosclerotic lesions of humans and rabbits (Yla-Herttuala et al, 1989).…”
Section: Lycopene 15mentioning
confidence: 99%
“…However, the closest explanation of Lp(a) biology, but not necessarily the correct one, likely has to do with the fact that the LPA gene has duplicated itself from the plasminogen gene, either to further enhance plasminogen activity or to act as a yin-yang balance to plasminogen pathophysiology. In fact, we have shown that the oxidized phospholipids that are primarily present on Lp(a) are associated with increased cardiovascular risk (21,22), but that the oxidized phospholipids present on plasminogen are associated with enhanced fibrinolysis in vitro and that higher levels are present post-myocardial infarction (23)(24)(25), a putative beneficial function to prevent thrombus propagation. In line with these relationships, several members of the plasminogenrelated coagulation cascade, including tissue plasminogen activator that activates plasminogen to plasmin, are also associated with higher risk of incident T2D (26)(27)(28)(29), another action that is seemingly opposed by elevated Lp(a) levels.…”
Section: Sotirios Tsimikas 2 Editorial Boardmentioning
confidence: 99%